Enhancing Agricultural Resilience: A WEFE nexus workshop on Conservation Practices and Scenario Design - Kertolli, Emirjona; Belhouchette, Hatem (CGIAR System Organization, 2024)
The Water-Energy-Food-Ecosystem (WEFE) nexus workshop on Conservation Practices and Scenario Design gathered agriculture stakeholders from the Meknes region, Morocco from October 17-18, 2024, in Montpellier, France. The objective was to develop a bioeconomic model-based integrated assessment framework (WEFE nexus) that will not only assess the current agricultural situation in Morocco but also evaluate the potential adoption of conservation agriculture (CA) practices by local farmers. By simulating various farm-level scenarios, we aim to identify the key economic, social, and technical barriers that may affect their decision to convert.